Patience in foraging-horticultural society: a test of competing hypotheses - Godoy, Ricardo; Byron, Elizabeth; Reyes-Garcia, Victoria; Leonard, William. R.; Patel, K.; Apaza, Lilian; Perez, Eddy; Vadez, Vincent; Wilkie, David (University of Chicago Press, 2004)
Patience, or the ability to delay gratification, matters in the behavioral and medical sciences and in public policy because it correlates with a wide range of desirable outcomes. For instance, patience correlates positively with income, wealth, conservation of natural resources, health, and savings and negatively with crime and drug addiction. Anthropologists have made few contributions to crosscultural studies of patience despite its importance. Drawing on five-quarter panel data from 154 Amerindians (10-80 years of age) from the Tsimane’ foraging horticultural society in the Bolivian Amazon, we use hyperbolic and exponential discounting to estimate patience and the correlation between patience and (a) modern human capital, (b) personal affluence, and (c) age. Levels of impatience in Tsimane’ society are higher than in Western societies. We find a strong negative correlation between schooling and impatience and a weaker, but still negative, correlation between impatience and modern human-capital skills. We find mixed support for (b), probably because of sharing and reciprocity. We also find mixed support for (c), probably because of a truncated sample and measurement error of the age variable. We discuss areas for future research to encourage anthropologists to contribute to the cross-cultural understanding of patience.